(untitled) (THE ACADEMIA, 2026)
This article explores the mathematical symmetry among these number types and their potential applications in economic modeling and decision-making. The study of mathematical sequences like Harshad numbers, Fortunate numbers, Lucky numbers, and Happy numbers offers a fascinating perspective on economic modeling. These numbers, while originating in pure mathematics, exhibit properties that can be mapped onto financial stability, market anomalies, and consumer behaviors. Future research can further explore how these numerical symmetries can enhance predictive economic models and decision-making frameworks. By integrating mathematical properties with economic principles, we can develop robust analytical tools that provide deeper insights into financial trends and policy-making, reinforcing the timeless connection between mathematics and economics.